IMPLEMENTASI KEBIJAKAN PROGRAM PEMBINAAN ANAK JALANAN DI KOTA SURAKARTA (STUDI KASUS PADA DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KOTA SURAKARTA) - Liliek Winarni, Anggiat Bimo Haryo S & (Transformasi, 2015)
Results of research policy implementation guidance program street children inSurakarta has been running well, where the program is implemented is the establishment ofkeroncong groups and free education for street children, and in supporting the programimplementation it is necessary implementers are Department of Social, Labour andTransmigration Surakarta. Implementation policy program guidance street children withEdward III known that internal communication between the Head of Department and Head ofSocial Rehabilitation has been shooting went well. Human resources development programimplementers street children in Surakarta has been able to carry out the implementation ofthe programs, but in the field of human resources in this staff, which is only one person, makea coaching program has not run optimally, while the field of financial resources for thedevelopment of children street comes from the budget and the lack of resources, the facilitiesSocial Services, Manpower and Transmigration Surakarta in collaboration with theDepartment of Education and Sports in the provision of education and training keroncong.The attitude of the executive coaching program policies street children are very influential, asseen from the employees' commitment to helping street children to get a better future byconducting educational programs and kroncong exercise and free from bureaucraticstructures implementing development programs already in charge of street children inaccordance with the respective respective duties, employees performing their duties inaccordance with the provisions of the run.Key Word: Policy; development; emplyeer; implementation